The Influence of Human Resource Competencies and Facilities on Hotel Occupancy: Consumer Satisfaction Mediation in Makassar City - Edi Jusriadi; Ambo Uleng (International Journal of Management Science and Information Technology, 2026)
The increasingly fierce competition in the hotel industry in Makassar City requires hotels to improve the quality of service through strengthening the competence of human resources (HR) and providing adequate facilities to increase consumer satisfaction and hotel occupancy rates. This study aims to analyze the influence of human resource competencies and hotel facilities on hotel occupancy rates with consumer satisfaction as a mediating variable. The study used a quantitative approach with a survey method of 62-star hotel guests in Makassar City who were selected using convenience sampling techniques. Data was collected through a structured questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to test the direct and indirect relationships between variables. The results of the study show that human resource competence has a positive and significant effect on hotel occupancy rates, but does not have a significant effect on consumer satisfaction so that satisfaction does not mediate the relationship. On the other hand, hotel facilities have a significant effect on consumer satisfaction, but do not have a direct effect on hotel occupancy rates, but have a significant indirect influence on occupancy rates through consumer satisfaction as a mediating variable. These findings suggest that improving the quality of facilities that are able to meet consumer expectations will increase customer satisfaction which ultimately drives an increase in hotel occupancy rates.